2020
DOI: 10.1177/0963689720947102
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Pig Sertoli Cells Survive Xenotransplantation by Creating an Immune Modulatory Environment Involving CD4 and CD8 Regulatory T Cells

Abstract: The acute cell-mediated immune response presents a significant barrier to xenotransplantation. Immune-privileged Sertoli cells (SC) can prolong the survival of co-transplanted cells including xenogeneic islets, hepatocytes, and neurons by protecting them from immune rejection. Additionally, SC survive as allo- and xenografts without the use of any immunosuppressive drugs suggesting elucidating the survival mechanism(s) of SC could be used to improve survival of xenografts. In this study, the survival and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 68 publications
1
30
0
1
Order By: Relevance
“…In addition, they act as immunological sentinels of spermatogenesis by not only forming the blood-testis barrier, but also expressing immunoregulatory factors [2]. Sertoli cell/islet cograft shows that the infusion of SCs into islet transplantation effectively prolonged the survival of islet grafts by reducing CD4 + and CD8 + T cells but increasing the CD4 + or CD8 + Tregs [109,110]. Interestingly, while syngeneic SCs help to impede CD8 + T cell infiltration through the formation of a tubule structure, allogeneic SCs fail to form this structure and prevent the infiltration of active immune cells, thus having a detrimental effect on islet graft survival [111].…”
Section: T Lymphocytes and Sertoli Cellsmentioning
confidence: 99%
“…In addition, they act as immunological sentinels of spermatogenesis by not only forming the blood-testis barrier, but also expressing immunoregulatory factors [2]. Sertoli cell/islet cograft shows that the infusion of SCs into islet transplantation effectively prolonged the survival of islet grafts by reducing CD4 + and CD8 + T cells but increasing the CD4 + or CD8 + Tregs [109,110]. Interestingly, while syngeneic SCs help to impede CD8 + T cell infiltration through the formation of a tubule structure, allogeneic SCs fail to form this structure and prevent the infiltration of active immune cells, thus having a detrimental effect on islet graft survival [111].…”
Section: T Lymphocytes and Sertoli Cellsmentioning
confidence: 99%
“…However, rejecting Sertoli cell/islet co-grafts showed increased numbers of macrophages and T cells ( 96 ). These results are mirrored in xenotransplantation experiments, in which ectopically grafted neonatal pig Sertoli cells were able to reduce the overall number of macrophages and CD3 T cells, and increase the number of Tregs ( 43 ).…”
Section: Sertoli Cell Protective Response In the Testis And Summary O...mentioning
confidence: 75%
“…Similar results were observed in vivo where neonatal pig Sertoli cells after transplantation under the kidney capsule of nonimmune suppressed rats inhibited complement activation, specifically C3 deposition and MAC formation ( 36 ). At the same time there was reduced migration of APCs and increased Treg migration that may be at least partly due to the presence of fewer anaphylatoxins (C3a and C5a) ( 43 ). CD59, CD46, CD55, and CD59 also play important roles in sperm development, transit through male and female reproductive tracts, and fertility ( 44 ).…”
Section: Sertoli Cell Protective Response In the Testis And Summary O...mentioning
confidence: 99%
“…Therefore, the physical sequestration of these antigens is a critical function of Sertoli cells and suggests that Sertoli polarization, including proper basal localization of the BTB, is vital for spermatogenesis . Beyond establishing the BTB, Sertoli cells also modulate the immune environment in general via the secretion of cytokines and other factors, as it has been shown that Sertoli cells can significantly enhance the success of xenotransplantation in other organs (Doyle et al, 2012;Dufour et al, 2003;Kaur et al, 2014Kaur et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%